Understanding protein physico-chemical properties, functionality, and mechanisms underlying texturization in extruded plant-based meat: a novel approach for optimum structure and mouthfeel - Flory, Jenna (Kansas State University, 2023)
Plant-based protein is a promising and growing sector of the food industry with retail sales of plant-based meat alone recently surpassing $5 billion in 2021. This growth is partially due to the rapid increase in “flexitarian” consumers. Flexitarians are people who eat meat but want to reduce their meat consumption due to a variety of reasons. Some common reasons of increased plant-based protein consumption are perceived benefits of plant-based foods including nutrition, sustainability, and animal welfare. One current major challenge restricting the widespread acceptance of plant-based meat by consumers is the texture of the product. Many flexitarians want a product that reminds them of traditional meat products so it can be easily incorporated into their everyday recipes and meals. This is a challenge because real meat structure can be difficult to replicate because of the fibrillar structure of the animal muscle. Many plant-based meat products are made using extrusion to cook and realign plant protein ingredients into a fibrous and layered piece that mimics meat texture. This research will utilize low-moisture extrusion to create texturized vegetable protein (TVP) that can then be combined with water, binders, oil, and seasonings to make a plant-based burger. TVP can be made from many different plant sources but some of the most popular are soy, pea, and wheat. This research aims to understand several key functionality attributes of plant protein sources, such as solubility and gelling capacity, to determine how they impact the quality of the final plant-based meat product. The results of the first study confirmed that proteins can be characterized into two categories: those that are soluble at room temperature (cold swelling) and those that are more soluble after heating (heat swelling). According to their swelling category, these proteins act differently in the extrusion process and produce meat analogues with different textures as shown by changes in bulk density, visual structure, and water holding capacity. Results show that bulk density was higher for treatments targeting a firm product (274 g/L, 287 g/L) than those targeting a soft (160 g/L, 223 g/L). Hardness as determined by texture profile analysis (TPA) also showed that soft targeting treatments seemed to show a lower hardness (1154 g, 1595 g) than the firm targeting treatments (2231 g, 1893 g), but there was a large standard deviation for each. More conclusive differences between proteins were found in the following study in Chapter 3 by using cooked plant-based patties for TPA and by confirming these results with a consumer sensory study and focus groups. This study was designed to include 6 treatments with increasing amounts of cold swelling proteins. WAI was highest for the 90% CS treatment at 5.61 g/g. On the other end, the lowest WAI was found to be from the 0% CS treatment at 2.51 g/g. Overall, it was shown that, as hypothesized, cold swelling proteins tend to produce a softer and more sponge-like product while heat swelling proteins create more densely packed layers and a firmer texture. By gaining a more thorough understanding of the solubility of different protein sources and making connections to how these properties impact the texture of plant-based meat analogues, product developers can use simple solubility information to predict outcomes and qualities of extruded plant protein products. This is vital as new plant-based products are being created with novel textures, and as current products are being improved to be more appealing to consumers. Industry can also benefit by using this swelling categorization method to maintain consistent product quality through the use of simple analytical methods such as WAI, LGC, and RVA to check ingredient consistency and functionality properties.
Keywords: Plant-based meat; Textured vegetable protein; Extrusion; Protein functionality